2007
DOI: 10.1094/cm-2007-0122-02-rs
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Mustard Green Manure on Potato Yield and Disease Incidence in a Rainfed Environment

Abstract: The goal of this work was to evaluate the short‐term effects of a mustard green manure on potato yield and disease incidence for potatoes grown in a rainfed cropping system. Diseases of interest were black scurf (Rhizoctonia solani), powdery scab (Spongospora subterranea), and white mold (Sclerotinia sclerotiorum). On‐farm trials with large (60‐ft wide) replicated plots were established at three sites in 2003 and 2004, in Maine. Mustard (Sinapis alba and Brassica juncea blend) was sown at a seed rate of 10 lb/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
1
7
1
Order By: Relevance
“…Data on incidence of common scab and Rhizoctonia were variable and did not show any significant treatment effects ( data not shown ). Previous work has shown that mustard green manure (not mustard seed meal) is associated with decreased incidence of Rhizoctonia, and in some cases with decreased incidence of common scab (9,18); however, in the current study using seed meals we did not observe a consistent effect on incidence of these diseases.…”
Section: Petiole Nitrate and Yield Datacontrasting
confidence: 99%
“…Data on incidence of common scab and Rhizoctonia were variable and did not show any significant treatment effects ( data not shown ). Previous work has shown that mustard green manure (not mustard seed meal) is associated with decreased incidence of Rhizoctonia, and in some cases with decreased incidence of common scab (9,18); however, in the current study using seed meals we did not observe a consistent effect on incidence of these diseases.…”
Section: Petiole Nitrate and Yield Datacontrasting
confidence: 99%
“…Data obtained in the present study are in accordance with previous investigations which showed that 2 or 3 yr cereal-potato rotations and GMs can reduce the occurrence of potato diseases, including black scurf [17,68,69] and common scab [16]. In the present study, the lowest incidence of black scurf and common scab was recorded for potato grown after summer GMs (mustard, japanese millet, and pearl millet).…”
Section: Incidence Of Common Scab and Black Scurfsupporting
confidence: 92%
“…In the present study, the lowest incidence of black scurf and common scab was recorded for potato grown after summer GMs (mustard, japanese millet, and pearl millet). The suppressive effects of these green manure crops on potato black scurf and/or common scab have been demonstrated in various studies reporting the control of potato diseases with pearl millet [70], japanese millet [68], and mustard [15,17]. As shown in the present study, these green manures also increased soil microbial activity (Table 6) which may result in increased competition for existing nutrients [18,71] or increased populations of antagonistic organisms against S. scabies [71,72] or R. solani [15].…”
Section: Incidence Of Common Scab and Black Scurfmentioning
confidence: 99%
See 2 more Smart Citations